Perlindungan Anak Pasca Perceraian: Analisis Pembatasan Hak Bertemu Ayah dalam Perspektif Hukum Keluarga Islam - Lhupiana Dewi; Zahwa Dzakiyyah; Nurlita Nurlita; Chindona Kanariansa; Muhammad Imam Raihan; Ariel Febrian (Journal of Sharia and Legal Science, 2025)
This study analyzes the restrictions on children's right to see fathers who misbehave from the perspective of Islamic family law. In the context of Islamic law, a child's right to receive affection and guidance from both parents is a fundamental right that must be protected. However, what if the father's behavior actually has a negative impact on the child's moral and psychological development? This is a qualitative study using a normative juridical approach. The results show that father involvement contributes significantly to the child's cognitive, emotional, and social development, but paternal misconduct can cause harm and psychological disorders. Islamic family law allows for proportional restrictions on the right to see children through court or supervisory mechanisms, to protect the child's welfare without completely eliminating the father's rights. This study emphasizes the principle of the best interest of the child as the primary guideline in decision-making regarding the right to see children.